Epidemiological Assessment of COVID-19 Clinical Symptoms and Its Associated Factors from Banten Districts: The Role of Gender Aspects - Sari, Flori R; Suwarsono, Erike A; Adhiyanto, Chris; Habibi, Ahmad Azwar; Siregar, Alyya Siddiqa; Ariany, Devy; Sahid, Muniroh; Jauharoh , Siti Nur Aisyah (Bangladesh Journal of Medical Science, 2022)
Objectives: The symptoms of COVID-19 resemble those of a variety of mild to severe clinical conditions. Having epidemiological knowledge of the clinical symptoms of COVID‑19 and associated factors may help health workers to diagnose and manage the disease. Assessment of COVID-19’s clinical symptoms is therefore necessary to support health workers in Banten, Indonesia. Materials and Methods: In this descriptive cross-sectional study, we purposively analysed 1492 medical records from our online COVID-19 database. All data were analysed in a consecutive manner and were shown as percentages or significances. Results: Medical records revealed that 577 patients (39%) were male and 915 (61%) were female. Our sample contained 106 patients (7%) who tested positive for COVID-19. Among these 106 patients, 70 were asymptomatic (66%) while the rest (34%) had single or multiple clinical symptoms. The most common symptom was fever (16%), followed by cough (15%), fatigue (11%), headache (11%), dysphagia (10%), rhinorrhoea (8%), nausea (7%), dyspnoea (4%) and diarrhoea (2%). Subsequently, gender differences were found to be significantly associated with positive cases (p<0.05), the appearance of clinical symptoms (p<0.05), and decision whether to hospitalize or self-isolate (p<0.05). Conclusion: Fever, cough and fatigue predominated in the COVID-19 symptoms reported by our patients. Additionally, gender differences should be carefully considered in developing better management processes. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 782-787